Efektifitas pendidikan kesehatan menggunakan metode pendidikan individual tentang pengetahuan Pola makan pada penderita hipertensi di puskesmas harapan raya - Suri Rahma Yeni; Siti Rahmalia HD; Oswati - Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this research was to determined the effectiveness of health education with individual aproach about knowledge of diet toward patient with hypertension. The design of this research was “Quasy experiment” The research conducted at puskesmas harapan raya Pekanbaru. This research used 30 Samples,  taken with purposive sampling technique. Wilcoxon signed rank test and mann whitney test was used to analysed the data. The result shoned that health education effect the knowledge of eating pattern in hypertension patient ( p value 0,000) < α(0,05). This research recommend to all health personel to give health education  with individual approach method to increase of knowledge toward patient with hypertension about diet to reduce other complication due to hypertension. Keywords : effectiveness education of health, individual method, knowledge of system meal, sufferer hypertension. References : 38 (2002-2013)